PERAN PEMERINTAH DAERAH DALAM PENGURANGAN RISIKO BENCANA MELALUI PENINGKATAN KETAHANAN BENCANA DAERAH DI KABUPATEN TANAH BUMBU - Zainuddin, Zainuddin; Kissinger, Kissinger; Kadir, Syarifuddin; Badaruddin, Badaruddin (Universitas Lambung Mangkurat, 2024)
Exploitation of natural resources triggers a decrease in the carrying capacity and capacity of the environment and results in climate change and various kinds of disasters. The objectives of this research are Analyzing the role of the Regional Government in implementing the Regional Resilience Index Improvement Program; Analyzing the inhibiting factors of the Regional Resilience Index improvement that has been carried out by the Tanah Bumbu Regency Government; Determining the priority scale of the Regional Disaster Resilience Improvement Program. Data analysis used in this study is Calculating the percentage of indicator achievement based on the Technical Guidelines for the Regional Resilience Index Assessment Tool, Descriptive analysis of inhibiting factors in increasing the Regional Disaster Resilience Index (71 Indicators) to stakeholders through interviews, Creating a priority scale matrix to determine recommendations. Determination of the priority scale matrix is based on Minimum Service Standards and ranking of relevant stakeholders. The results of research on the role and inhibiting factors of the Tanah Bumbu district government in increasing the Regional Resilience Index are Indicators implemented in the priority of Strengthening Policies and Institutions by 60.00%. Indicators implemented in the priority of Risk Assessment and Integrated Planning amounted to 75.00%. Indicators implemented in the Information System Development, Training and Logistics priority by 69.23%. Indicators implemented in the priority of Thematic Handling of Disaster Prone Areas amounted to 80.00%. Indicators implemented in the priority of Increasing the Effectiveness of Disaster Prevention and Mitigation by 70.00%. Indicators implemented in the priority of Strengthening Disaster Preparedness and Emergency Management by 55.00%. Indicators implemented in the Disaster Recovery System Development priority of 75.00%.